Span analysis of optical fiber transmission based on WDM , DWDM and DQPSK - Kabir, Humayun; Faruq, Asaduzzaman All; Reza, Tanvir (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.